Behavioural characterisation of Holstein steers in three different production systems - Blumetto, O.; Ruggia, A.; Dalmau, A.; Estellés, Fernando; Villagrá, Arantxa (CSIRO Publishing, 2021)
The objective of the present study was to characterise the behaviour of Holstein steers in three different production systems. Forty-eight castrated Holstein males were randomly divided into three groups and allocated to the following three outdoor treatments: (T1) animals confined in a yard with an area of 210 m2, (T2) animals confined in a similar-sized yard but with 6 h of access to a pasture plot, (T3) animals maintained throughout the experiment on a pasture plot. Behaviour was recorded by scan sampling, 12 h a day (from 0700 hours to 1900 hours), 3 days per week, for 4 weeks evenly distributed from Week 7 to Week 16 of the experiment. So as to assess their patterns of behaviour, a negative binomial regression, correspondence analysis and logistic regressions were performed. Grazing was the predominant behaviour among Groups T2 and T3, while ‘eating hay’ was the most frequent behaviour among Group T1. For all treatments, lying was the second-most frequent behaviour. Despite animals in T2 having access to pasture for only half of the time with respect to those in T3, there was no difference between both treatments in the time spent grazing. Correspondence analysis of behaviour as a function of weather conditions showed that several behaviours were close to certain weather conditions, e.g. ‘standing’ and ‘ruminating while standing’ were closer to light rainy weather, while ‘lying’ or ‘ruminating while lying’ were more related to sunny weather.’Lying’ tended to increase along the day in all treatments, while ‘eating hay’ increased along the day within Group T1, but decreased within Groups T2 and T3. It is concluded that the management conditions associated with the systems that were studied produced different behavioural patterns in the steers. Grazing behaviour is important for the animals, and the permanent or restricted possibility to perform it, determined by the production system, meant that the patterns of other behaviours changed to give priority to pasture intake.